THE PREREQUISITES, APPLICATION AND PROSPECTS FOR THE USE OF THE HARDENING METHOD OF ELASTIC AND PLASTIC DEFORMATION - Kartashev, V. V. (Science and Transport Progress, 2006)
The paper is devoted to development of advanced technologies, which allow choosing an optimum mode of hardening of the wagon cast parts by the method of elastic-plastic deformation.